[Breaking up is hard ; A question of arms ; Anything is possible [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Looks into the alternatives to the bases of the U.S. announced pull-out from Clark; issues on gunless society; and an interview with Debbie Gibson a teeny bopper sensation in the U.S.
Breaking up is hard (17 min.) -- A question of arms (16 min.) -- Anything is impossible (13 min.)
VHS.
Keywords: Gibson, Debbie; Military bases, American -- Philippines; Firearms -- Philippines; Gun control -- Philippines; Angeles City -- Economic conditions